Eleanor and Franklin the story of their relationship, based on Eleanor Roosevelt's private papers - Lash, Joseph P. 1909-1987. (New York W.W. Norton & Co., 1971)
Gives insight into Eleanor's childhood, how she overcame personal insecurity, how she coped as a politician's wife, and describes her relationship with her husband, Franklin.
Foreword by Arthur M. Schlesinger, Jr. -- Introduction by Franklin D. Roosevelt, Jr. -- Author's note -- Preface -- Childhood and youth -- Wife and mother -- The emergence of Eleanor Roosevelt -- the White House years -- Bibliographical note -- References -- Index.
Included in the Dean Bonifacio Salamanca Collection.
Includes bibliographical references (pages 728-750) and index.
Pulitzer Prize, Biography, 1972.
Society of American Historians Francis Parkman Prize, 1972.
Keywords: Roosevelt, Eleanor -- 1884-1962.; Roosevelt, Franklin D. -- 1882-1945.; Presidents' spouses -- United States -- Biography; Presidents -- United States -- Biography; Biography. fast (OCoLC)fst01423686.